1999
DOI: 10.1029/1999wr900277
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various water quality sampling strategies on load estimates for small streams

Abstract: Abstract. Extensive streamflow and water quality data from eight small streams were systematically subsampled to represent various water-quality sampling strategies. The subsampled data were then used to determine the accuracy and precision of annual load estimates generated by means of a regression approach (typically used for big rivers) and to determine the most effective sampling strategy for small streams. Estimation of annual loads by regression was imprecise regardless of the sampling strategy used; for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
162
1
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(168 citation statements)
references
References 18 publications
3
162
1
2
Order By: Relevance
“…On average these were AE25% for TN and TP, and up to 50% for SS and were similar to other estimates of uncertainty (e.g. Robertson and Roerish 1999).…”
Section: Loads and Yieldssupporting
confidence: 69%
See 1 more Smart Citation
“…On average these were AE25% for TN and TP, and up to 50% for SS and were similar to other estimates of uncertainty (e.g. Robertson and Roerish 1999).…”
Section: Loads and Yieldssupporting
confidence: 69%
“…Stream loads leaving four of the catchments were initially calculated using the products of flow-weighted mean concentrations (the sum of simultaneous products of concentration and stream flow divided by the sum of the individual flows) from the monitoring data, and true mean flow for each period from the continuous flow record (Ferguson 1987;Robertson and Roerish 1999). Because continuous flow measurements in Waikakahi Stream began in 2001, load estimates for 1996-1998 were made using individual flow measurements made at each time of sampling, and using the 2001-2011 mean annual flow (Table 1) to approximate the 1996-1998 period.…”
Section: Loads and Yieldsmentioning
confidence: 99%
“…1) to determine whether monthly sampling from one site adequately described stream water quality and enabled accurate estimates of loads and specific yields. Robertson and Roerish (1999) concluded that 'for study durations of two or more years, routine fortnightly sampling is likely to give the least biased and most precise load estimates. Furthermore, additional high-flow samples result in imprecise, overestimated annual loads if samples are consistently collected early in high-flow events'.…”
Section: Study Areamentioning
confidence: 99%
“…Storm-flow concentrations of SS, TN and TP were recorded and relationships with flow evaluated in order to calculate storm loads (Ferguson 1987;Robertson and Roerish 1999). Loads were calculated using percentile flows to weight the contributions from routine monitoring and from flood flows.…”
Section: Load Calculationsmentioning
confidence: 99%
See 1 more Smart Citation